Drivers and patterns of antibiotic use in small to medium-sized chicken farms in selected districts of Nepal - Adhikari, Jeevan; Thapaliya, Sharada; Munakarmi, Reshmi; Acharya, Pawan; Basnet, Hom Bahadur; Paudyal, Narayan (Frontiers in Veterinary Science, 2025)
The rise in commercial poultry production in Nepal has led to inappropriate and haphazard use of antibiotics, contributing to antimicrobial resistance (AMR). This study aimed to identify the drivers influencing antibiotic use among small to medium-scale layer chicken farms in selected districts. A cross-sectional questionnaire survey was conducted among 180-layer poultry farmers in Makawanpur (n = 45), Chitwan (n = 30), Dang (n = 46), and Pokhara (n = 59). Data were analyzed using descriptive statistics and multivariable logistic regression analysis. Among the 346 responses, antibiotics were used for treatment (50.6%), prophylaxis (32.7%), growth promotion (4.6%), improving egg laying (2.6%), and viral infections (9.5%). Antibiotics were administered during brooding (33.8%), debeaking and vaccination (30%), disease epidemics (23.8%), transportation (7.5%) and shifting of houses (5%). Only 39.1% of decisions regarding antibiotic usage were based on laboratory reports; others relied on professional experience (25.8%), necropsy findings (23.4%), or telemedicine consultations (11.7%). Correct dose measurement using graduated dispensers was reported in only 27.2% of responses. Fluoroquinolones were the most used (22.2%), followed by tetracyclines (19%) and macrolides (17.6%). The multivariable logistic regression analysis revealed that poor biosecurity scores and higher stress levels in birds significantly increased antibiotic use at the farm level. Our findings indicate that inadequate knowledge among poultry producers leads to inappropriate antibiotic use beyond therapeutic purposes. Poor biosecurity practices and stressors are major factors associated with increased antibiotic usage. Creating antimicrobial resistance awareness and promoting responsible use of antibiotics among farmers is essential. An integrated national AMR and food safety policy, including farmer education and strict guidelines, would be beneficial.